PENGARUH KERAGAMAN PRODUK, KUALITAS LAYANAN TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN SHOPEE PADA MAHASISWA FAKULTAS EKONOMI UNIVERSITAS ABDURACHMAN SALEH SITUBONDO DENGAN MINAT BELI PRODUK FASHION MUSLIM SEBAGAI VARIABEL INTERVENING - Faradila, Sofia Mirza; Kusnadi, Edy; Soeliha, Siti (Jurnal Mahasiswa Entrepreneurship (JME), 2022)
The development of increasingly sophisticated technology has resulted in changes in people's lifestyles in online shopping activities which are an option for some people due to the density of activities. The increasing growth of the e-commerce market in Indonesia has caused business actors to compete to switch to selling products in the electronic commerce market. The purpose of this study was to analyze and examine the effect of product diversity, service quality on Shopee consumer purchasing decisions with interest in buying Muslim fashion products. This research is a quantitative approach. The population in this study were students of the Faculty of Economics and Business, Abdurachman Saleh University, Situbondo. The sampling technique used is Probability Sampling by choosing the Proportionate Stratified Random Sampling technique. Data analysis and hypothesis testing in this study used the Structural Equation Model-Partial Least Square (PLS-SEM). The results of the direct influence hypothesis test using the Smart PLS 3.0 application, indicate that product diversity has a significant positive effect on purchase intention, product diversity has a significant positive effect on purchasing decisions, service quality has a significant positive effect on buying interest, service quality has a significant positive effect on purchasing decisions, interest buying has a significant positive effect on purchasing decisions. The results of the indirect effect hypothesis test show that product diversity on purchasing decisions through buying interest has a significant positive effect, service quality on purchasing decisions through buying interest has a significant positive effect.